Optimization Model for Location of Rfid Antennas in a Supply Chain - Soto-Gomez, J; Alfaro-Marchant, M; Carrasco-Armijo, R; Fuertes-Sanchez, G (Institute of Electrical and Electronics Engineers Inc., 2018)
It is presented the methodology to place properly height antennas over the surface of a storage cellar, in a link of electromagnetic waves between an identification radio frequency antenna (RFID) and a Passive label starting from a radioelectric profile. It is described the effect of different external dimensions and distributions of the internal space over the signs of radio frequency; the parameters used and the analyzes of the system are adjusted to a dynamic real model of transmission. The main objective of this study is to determine the sturdiness of a genetic algorithm using a simple model of communication which finds the suitable position of the antenna and allows the needed polarization for the identification of all the passive RFID labels, using as measure the minimum power received by the RFID. Through a location model and with the help of a genetic algorithm (GA), it is searched the proper position of the antennas that allows the need polarization for the identification of all the labels, using as a measure the minimum power received by the RFID antenna. © 2018 IEEE.